Exogenous Urokinase Inhibits Proteasomal Degradation of Its Cognate Urokinase Plasminogen Activator Receptor - Zhu, Ran; Liu, Ting-Wei; Liu, Fan (Frontiers in Pharmacology, 2022)
Acute pulmonary embolism (APE) is a debilitating condition with high incidence and mortality rates. APE is widely treated with the serine protease urokinase or urokinase-type plasminogen activator (uPA) that functions by resolving blood clots via catalyzing the conversion of plasminogen to plasmin. Treatment with recombinant uPA has been shown to increase endogenous expression of uPA and its cognate receptor, uPAR; however, the mechanisms for this induction are not known. Using an in vitro hypoxia/reoxygenation model in bronchial epithelial BEAS-2B cells, we show that induction of hypoxia/reoxygenation induces apoptosis and increases secretion of tumor necrosis factor–alpha, brain natriuretic peptide, and fractalkine, which are attenuated when treated with exogenous uPA. Induction of hypoxia/reoxygenation resulted in decreased expression of uPAR on cell surface without any significant changes in its messenger RNA expression, highlighting post-transcriptional regulatory mechanisms. Determination of uPAR protein half-life using cycloheximide showed treatment with uPA significantly increased its half-life (209.6 ± 0.2 min from 48.2 ± 2.3 min). Hypoxia/reoxygenation promoted the degradation of uPAR. Inhibition of proteasome-mediated degradation using MG-132 and lactacystin revealed that uPAR was actively degraded when hypoxia/reoxygenation was induced and that it was reversed when treated with exogenous uPA. Determination of the proteolytic activity of 20S proteasome showed a global increase in ubiquitin–proteasome activation without an increase in proteasome content in cells subjected to hypoxia/reoxygenation. Our results cumulatively reveal that uPAR is actively degraded following hypoxia/reoxygenation, and the degradation was significantly weakened by exogenous uPA treatment. Given the importance of the uPA/uPAR axis in a multitude of pathophysiological contexts, these findings provide important yet undefined mechanistic insights.